God and Justice in Hesiod and Plato: Interpreting the Myth of Protagoras (Prot. 320d-322d) - Konrádová, Veronika (ΠΗΓΗ/FONS, 2019)
The paper examines the interconnection between fundamental principles of human socia-bility and the element of the divine. Specifically, it focusses on the close connection between the notions of god and justice, established in the works of pre-philosophical and philosophical tra-ditions, namely Hesiod and Plato. Special attention is paid to motives, which may be shared by Hesiod and Plato regarding principles underlying human social and political life. The examina-tion opens with a reference to Hesiod’s image of Zeus as a guarantee of justice, enabling a fully human and well-ordered communal life (Hes. Op. 213-285). On this basis, the question is raised to what degree Plato draws from this basic image and to what extent he prolongs Hesi-od’s vision in his own writings. The answer is sought in a detailed analysis of the myth of the origins of culture in Plato’s Protagoras (Prot. 320d-322d). Among other Hesiodic echoes, the passage contains Zeus’ key image providing humankind with justice and shame, i.e. indispen-sable principles of social life in the cities. Concerning the authorship problem of the whole nar-ration, presented by Protagoras in the dialogue’s dramatic setting, the paper defends the posi-tion that the story is Platonic in its essential points. Arguments in favour of this conviction in-clude: 1) detection of significant differences in comparison with other pieces of sophistic treat-ment of the issue of the origins of culture (in this respect, the Sisyphus fragment B25 will be ex-amined in particular), 2) highlighting elements of Platonic anthropology and theology present in the myth. Here, a significant reference point is Plato’s Laws, especially a long exposition on threats of atheism in Book 10 (889a-906c), refusing conventionalism as an explanatory model of political co-existence. With a thorough textual analysis, the paper aims to show how Plato develops and transforms the conception of underlying principles of human sociability, both in response to his predecessors and in confrontation with ongoing contemporary discussion. The proposed interpretation emphasises god’s fundamental role in the arrangement of human af-fairs, as a constant feature of Plato’s treatment of the issue, also recognisable in the structure of Protagoras’ myth.
Keywords: Hesiod; Plato; Protagoras; myth; origin; culture; god; justice